Pengelolaan Arsip Aktif Menggunakan Aplikasi Surat Menyurat Elektronik Aplikasi Negara (SULTAN) di Dinas Perpustakaan dan Arsip Kabupaten Bandung Tahun 2024 - Delia Putri Anggita; Nandang Alamsah Deliarnoor; Andi Kasman (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Active archives are needed to support the administrative and bureaucratic activities of each agency, which serves as the center of memory, decision-making tools, and authentic evidence of the agency. memory, decision-making tools, and authentic evidence of the agency. institution. This study discusses active archive management using the State Application Electronic Correspondence (SULTAN) application at the Bandung Regency Library and Archives of Bandung Regency in 2024. The study This study uses qualitative methods because of several considerations, namely first, first, this method presents the nature of the relationship between the reviewer and the respondent directly; and respondents directly; and by using this method, the reviewer can balance the value patterns to be studied. patterns of values that want to be studied more deeply. The data collection techniques used data collection techniques used were observation, interviews, and document studies, which were then processed using the technique of source triangulation to review information. triangulation technique to review the information.The results showed that although this application helps in the efficiency of active archive management, there are still several obstacles that cause active archive management which includes the process of creation, management and control, as well as the process of use and maintenance to not be fully implemented according to applicable regulations. This obstacle is often caused by features in the SULTAN application that are still not in accordance with archival principles. In addition, archival human resources (HR) who do not optimize the use of applications so that there are still many archives that are still managed conventionally. Seeing the existing problems can cause the risk of hampering active archive management in the SULTAN application. This study provides recommendations to improve the efficiency of active archive management using the SULTAN application at the Bandung Regency Library and Archives Office.